Association of age, race, and ethnicity with access, response, and toxicities from CAR-T therapy in children and adults with B-cell malignancies: a review - Marco Ruella; Guido Ghilardi; Zainul S. Hasanali; Sandra P. Susanibar-Adaniya; Lena E. Winestone; Alfred L. Garfall (Journal for ImmunoTherapy of Cancer)
Chimeric antigen receptor T cell (CAR-T) therapies are now standard-of-care for several B-cell malignancies, and additional indications are being evaluated. In this review, we survey data on how outcomes after CAR-T therapies vary according to age, race, and ethnicity. We also review the representation of age, racial, and ethnic groups in key CAR-T clinical trials. We focus on B-cell acute lymphoblastic leukemia, B-cell non-Hodgkin’s lymphoma, and multiple myeloma.